Registration and calibration in augmented reality for therapy - Wong, Thong Seng. (2008)
Augmented Reality is a technology in which a computer-generated image is superimposed onto the user's vision of the real world, giving the user additional information generated from the computer model. A potential application of augmented reality is to assist a surgeon pre-operatively and intra-operatively by enhancing his vision with computer-generated imagery so that he can see the target organ, the point of opening and the direction of cut etc.. Given the stereo images of the patient and a 3D model of the organ of interest, the main problem of augmented reality for medical therapy (ART) is to render the model and overlay it accurately onto the stereo image of the patient.